USAHA MENGGAPAI KESALEHAN DALAM ISLAM - Yuwono, Yohanes H. (LOGOS, 2004)
An effort to gain holiness is a spiritual activity. In Islam, this spiritual activity cannot be done out of exoteries deeds, that is why it looks real and visible, especially in our country where Muslims are majority; this activity is performed by most of our countrymen and countrywomen, so it attracts the mass media to report. The direct consequent is that the faithful of other religions, especially the Christians feel themselves as outsiders. As they watch their Muslim brothers and sisters doing their devotion, they (at least in their hearts) criticize, judge and make comparison with their religious pieties. To know the deep meaning of islamic pieties first of all we have to understand the spirituality of Islam so that we can avoid unfair and subjective comparison. This study is intended to widen our horizon of mind and as we learn from our Muslim brothers and sisters let us practice our piety intensively as they do.